Examining the female immigrant and minority representation in Shunji Iwai’s “Swallowtail Butterfly” - Çılgın, Pelin (İstanbul Bilgi Üniversitesi, 2023)
ABSTRACT: This article explores the representation of female immigrants and minorities in the film Swallowtail Butterfly (Shunji Iwai, 1996) from a multidisciplinary perspective. Starting with the topics related to being a foreigner/local, such as language nuances or the concept of furusato, the article then offers a new lens to look at the film and its female stories with the help of feminist theory. Therefore, this article aims to provide a comprehensive analysis of the film from current multiple-perspectives, as such a comprehensive analysis is highly needed in this contemporary age of rapid globalization

ÖZET: Bu makale, Swallowtail Butterfly (Shunji Iwai, 1996) filmi bağlamında kadın mülteci ve azınlık temsilini çok-disiplinli bir açıdan incelemektedir. Filmin furusato veya dil bariyerleri gibi yerli/yabancı temasını ilgilendiren konularıyla başlayan makale, ardından filmin kadın hikayelerini feminist teori ile incelemektedir. Dolayısıyla bu makale, küreselleşmenin hızla yaşandığı günümüzde, çoklu açılardan filmin güncel bir perspektifle kapsamlı bir analizini sunmayı amaçlamaktadır.
Shunji İwai’ın “Swallowtail Butterfly” filmi üzerinden kadın mülteci ve azınlık temsilinin incelenmesi
Keywords: Japanese studies; female immigrant and minority representation; furusato; the mother-whore dichotomy; women in urban spaces; Japon çalışmaları; kadın mülteci ve azınlık temsili; anne-fahişe ikilemi; kentsel mekânda kadınlar